E-care sentinel: ECG-based emergency alerts - Hashim, Rosziana; Ahmad, Suziana; Raymond Tanny, Gloria; Abdul Hadi, Dayanasari; Ahmad Aina, Ahmad Ali; Mohd Rasdi, Ahmad Firdaus; Ahmad Khairi, Muhammad Harries Ezary (Universiti Teknologi MARA, Kedah, 2023)
The electrocardiogram (ECG) is a vital biosignal extensively used in healthcare for pulse monitoring and health evaluation. This project takes ECG signals for heart rate by exploring inventive methods involving ESP8266 and Internet of Things (IoT) technology to create emergency alert systems. The primary goal of this project is to design an IoT-based Personal Emergency Response System utilizing ECG signals. The study involves the analysis of data from the ECG simulator MS400 to categorize heart rate conditions, including bradycardia, normal, and tachycardia. Three ECG signals for heart rate, measuring 40 BPM, 80 BPM, and 120 BPM, are selected as sample signals for analysis. The simulator data serves as the reference input. The ESP8266 microcontroller is employed to gather inputs and classify the ECG signals based on heart rate conditions. The outcomes are presented through the Blynk Application on smartphones and an integrated LCD display. The project undergoes functional testing to validate its effectiveness. Utilizing the ECG reference input, the project effectively functions as an alert system. It successfully indicates three heart conditions: bradycardia, normal, and tachycardia, presenting this information through both mobile apps and hardware displays such as LCD and LEDs.